Percepción del paciente con pie diabético sobre su imagen corporal hospital II Minsa -Tarapoto, periodo abril - julio 2013 - Bartra Jiménez, Delmira (2013)
The present study entitled "Perceptions of patients with diabetic foot on body image in the Hospital II MINSA-Tarapoto, period April-July 2013", conducted by researchers Bach. Enf. Delmira Bartra Jimenez and Bach. Enf. Graziella Hesperis Hervias Coba, aimed: To determine the perception of patients with diabetic foot on body image in the physical, psychological and social. The research raised was quantitative, applied, descriptive cross-sectional, we worked with simple descriptive design and the sample consisted of 50 patients with diabetic foot patients and amputees. To measure the variable perception of diabetic foot patients about their body image was used as the interview technique and an instrument a modified form of Likert type scale. From the results obtained in the study is concluded with the following: in terms of the perception of diabetic foot patients about their body image, 78% (39) had unfavorable perception and 22% (11) positive perception. Referring to the aspects: physical 70% (35) had unfavorable perception and 30% (15) positive perception in the psychological 56% (28) had unfavorable perception and 44% (22) positive perception and social 96% (48) had unfavorable perception and 4% (2) favorable perception. So it is concluded that the hypothesis is rejected study because most have unfavorable perception, based on physical appearance by stating that before amputate the limb were more attractive, in the psychological aspect because they think they might lose mortifies elsewhere in the lower extremity and the social aspect feel to be a burden to his family, and his family feel disinterest when asked for assistance for an activity. However, there is a smaller percentage having a favorable perception in the physical appearance indicating that although some do not have the bottom end, but I assume and feel comfortable using crutches and / or wheelchair, in the psychological aspect not uncomfortable to talk about their health with others and the social aspect not dislike her new look and well in the company of his family because they are the best support to go ahead with the disease. By which it is recommended that as nursing professionals empower your emotional situation such patients, since they need more mental attention, accept their situations to cope with the loss of a limb, with the collaboration of the patient and family.